Problem Based Pharmacotherapy Teaching for Pharmacy Students and Pharmacists - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2013)
Pharmacy profession also involves identifying, solving and preventing drug-related problems, as well as encouraging proper use of medications, thus improving clinical outcome of the treatment. Pharmacotherapy is usually thaught as lectures in pharmacy schools and many students have a difficulty in implementing the theoretical knowledge into practice. Therefore courses on rational drug use or rational pharmacotherapy should be given by problem based teaching methods. Since 2009, Rational Drug Use courses are given in Marmara University School of Pharmacy by such a method (based on simulated patients and dispensing score) developed by the 'Turkish Pharmacological Society'. The method enables problem based learning and it is also used in some of the pharmacy schools in Turkey and in Near East University in Northern Cyprus. This kind of learning will provide ability for critical thinking, improve problem-solving skills and decision making during pharmacotherapy.
Keywords: Dispensing score; pharmacist; pharmacy practice; pharmacy student; rational use of medicine; problem based pharmacotherapy; SCHOOLS